Evidence-Based Medicine in Otolaryngology, Part XIII: Health Disparities Research and Advancing Health Equity. (June 2022) - Megwalu, Uchechukwu C.; Raol, Nikhila P.; Bergmark, Regan; Osazuwa-Peters, Nosayaba; Brenner, Michael J.
Objective: To provide a contemporary resource for clinicians and researchers on health equity research and implementation strategies to mitigate or eliminate disparities in health care. Data Sources: Published studies and literature on health disparities, applicable research methodologies, and social determinants of health in otolaryngology. Review Methods: Literature through October 2021 was reviewed, including consensus statements, guidelines, and scientific publications related to health care equity research. This research focus provides insights into existing disparities, why they occur, and the outcomes of interventions designed to resolve them. Progress toward equity requires intentionality in implementing quality improvement initiatives, tracking data, and fostering culturally competent care. Priority areas include improving access, removing barriers to care, and ensuring appropriate and effective treatment. Although research into health care disparities has advanced significantly in recent years, persistent knowledge gaps remain. Applying the lens of equity to data science can promote evidence-based practices and optimal strategies to reduce health inequities. Conclusions: Health disparities research has a critical role in advancing equity in otolaryngology–head and neck surgery. The phases of disparities research include detection, understanding, and reduction of disparities. A multilevel approach is necessary for understanding disparities, and health equity extensions can improve the rigor of evidence-based data synthesis. Finally, applying an equity lens is essential when designing and evaluating health care interventions, to minimize bias. Implications for Practice: Understanding the data and practices related to disparities research may help promote an evidence-based approach to care of individual patients and populations, with the potential to eventually surmount the negative effects of health care disparities.